Report on the Outcome of the FATF Plenary Meeting and Proposal for the Endorsement of the Methodology for Assessing Compliance with Anti-Money Laundering and Combating the Financing of Terrorism Standard. (Policy Papers; Policy Paper ;, 2002)
NULL.